Cultura, Civilización y Ultramodernidad: A propósito de Norbert Elias - Muñoz Martínez, Fernando (Logos. Anales del Seminario de Metafísica, 2005)
The sociological work of Elias is studied, together with his characteristic outcast position, typical of judaism at the end of the century. From such judaic root stems the metapolitical approach observed in the process of civilization from the platform of a Human Genre already assume as formed and defined by the civilized conscience. The idea of a metapolitical (extraterritorial) platform is determined, and its possible historical and political efficiency. Finally, the work focuses on the limits of the civilization process, contrasting N. Elias and G. Bueno conceptions on the issue. Hence a third alternative which observs such limit of history and its superation in the “antropological field” – through the a structural, technoscientific and objective development of society – springs as a source from where the “ultramoderne spirit” described at the end of the issue finds its origins.